CRIME OF STALKING IN THE FORM OF A THREAT TO PSYCHOLOGICAL INTEGRITY:: case law analysis of the STJ regarding the element repeatedly as a parameter for establishing the initial term of consummation (REMUNOM, 2025)
In the context of increasing social violence against women, the crime of stalking, provided for in art. 147-A of the Penal Code, also known as Stalking, was created. It is characterized by the conduct of repeatedly pursuing someone, affecting certain legal assets, including physical and psychological integrity. In this context, the doctrine expresses concern regarding the possible subsumption of conduct that may be considered socially normal, considering that it is a habitual crime, and is subject to punishment under the aforementioned criminal type. In this regard, in the context of the application of the criminal norm to the conduct of each specific case, the debate arises about when the crime may be considered consummated, considering its habitual nature.The purpose of this study is to discuss the parameters that should be considered to determine whether the crime of stalking has been consummated. The methodology employed is hypothetical-deductive, with a qualitative approach based on descriptive research, combined with jurisprudential analysis. It is concluded that the legal enforcer must possess a certain degree of discretion, taking into account the habitual nature of the conduct and the severity of the offense to the victim's psychological health, although there is a need to establish minimum objective parameters as a requirement for recognizing the completion of the conduct.